On the mode-segregated aerosol particle number concentration load : contributions of primary and secondary particles in Hyytiälä and Nanjing - Kulmala, Markku; Luoma, Krista; Virkkula, Aki; Petäjä, Tuukka; Paasonen, Pauli; Kerminen, Veli-Matti; Nie, Wei; Qi, Ximeng; Shen, Yicheng; Chi, Xuguang; Ding, Aijun (Finnish Environment Institute, 2016)
Aerosol particle concentrations in the atmosphere are governed by their sources and sinks. Sources include directly-emitted (primary) and secondary aerosol particles formed from gas-phase precursor compounds. The relative importance of primary and secondary aerosol particles varies regionally and with time. In this work, we investigated primary and secondary contributions to mode-segregated particle number concentrations by using black carbon as a tracer for the primary aerosol number concentration. We studied separately nucleation, Aitken and accumulation mode concentrations at a rural boreal forest site (Hyytiala, Finland) and in a rather polluted megacity environment (Nanjing, China) using observational data from 2011 to 2014. In both places and in all the modes, the majority of particles were estimated to be of secondary origin. Even in Nanjing, only about half of the accumulation mode particles were estimated to be of primary origin. Secondary particles dominated particularly in the nucleation and Aitken modes. Peer reviewed